(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2016)
The chemical composition of four edible plant foods species, three fish species and one prawn were analyzed in Food Chemistry Laboratory of Behbahan Khatam Alanbia University of Technology, Behbahan, Iran in 2014. The analysis of fatty acid and sugars composition were performed by gas liquid chromatography and high performance liquid chromatography, respectively. Protein and lipid content were founded higher in baked and fried in fish S. commersonnianus (74.29%), (20.20%), fish Sphyraena helleri (88.12%) and (17.77%), respectively. Ash content in fish S. commersonnianus varies from 9.80% to 15.34%, and in fish S. helleri from 5.83% to 7.68%. Based on the proximate analysis, it can be calculated that an edible portion of 100 g of studied edible plant foods provides, on average, around 303.9±1.04 kcal. The plant Portulaca neglecta is suitable for high temperature food processes. The macronutrient profile in general revealed that the wild plant foods were with rich sources of protein and carbohydrates, and had low amounts of fat. The highest protein, the lowest fat and energy contents were found in boiled in both fish species; therefore, boiling can be recommended as the best cooking method for healthy diet. Int. J. Agril. Res. Innov. & Tech. 5 (2): 82-85, December, 2015